2010
DOI: 10.2320/matertrans.maw201022
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Fe-Based Amorphous Coating Films by Thermal Spraying Technique

Abstract: Some amorphous Fe-Cr-P-C coating films having high hardness and high corrosion resistance have been produced by a newly developed thermal spraying technique. In order to control the temperatures of the powder particles in the flame spray and the substrate, a newly developed cylindrical nozzle, with external cooling nitrogen gas, was mounted to the front end of the thermal spraying gun. Fe 70 Cr 10 P 13 C 7 films with various external cooling gas velocities between 20 m/s and 40 m/s exhibited entire amorphous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Corrosion testing has demonstrated that the Fe-10Cr-based amorphous coating film exhibited a high corrosion resistance equal to that of Hastelloy C and commercially produced pure titanium. 3) High corrosion resistance of the Fe-35Cr-based amorphous coating film was observed in immersion tests using 35% hydrochloric acid. 4) For practical applications of these Fe-based amorphous coating films, the most important point is improvement of the adhesion strength between the sprayed coating films and the substrates, which may depend on the structure of the sprayed coating films and the density of the pores in the boundary region between the sprayed coating films and the substrates.…”
Section: Introductionmentioning
confidence: 97%
“…Corrosion testing has demonstrated that the Fe-10Cr-based amorphous coating film exhibited a high corrosion resistance equal to that of Hastelloy C and commercially produced pure titanium. 3) High corrosion resistance of the Fe-35Cr-based amorphous coating film was observed in immersion tests using 35% hydrochloric acid. 4) For practical applications of these Fe-based amorphous coating films, the most important point is improvement of the adhesion strength between the sprayed coating films and the substrates, which may depend on the structure of the sprayed coating films and the density of the pores in the boundary region between the sprayed coating films and the substrates.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, these carbides are widely used for producing ceramic-metal composite coatings on the substrate by conventional hardfacing techniques, such as thermal spraying, plasma spraying, electroslag remelting and arc welding, to improve wear resistance. [1][2][3][4][5] However, the surface coating produced by these technique had some disadvantages, such as the composite coatings with porosities, excessive energy input, the mechanical bonding between the composite coating and the substrate. In recent years, laser cladding technique has been developed and can avoid these disadvantages of the conventional surface techniques mentioned above by choosing optimal parameters.…”
Section: Introductionmentioning
confidence: 99%
“…So the corrosion resistance of the Fe 70 Cr 10 P 13 C 7 amorphous coating film did not enough for the practical applications such as the shaft sleeve of the slurry pump. 16) In the present study, high chromium Fe-Cr-Mo-P-C amorphous coating films containing up to about 35 at% Cr having excellent high hardness and high corrosion resistance have been produced by the thermal spraying technique with the cylindrical nozzle on shaft sleeve shaped cylindrical SUS304 substrates without cracking and peeling conditions. Corrosion tests of the sprayed films were also done under the severe immersion conditions of 35% hydrochloric acid.…”
Section: Introductionmentioning
confidence: 99%